Competency-based approach to education for a labor society - Jara Guerrero, Miriam Elizabeth (2025)
This article aimed to understand the development of the competency-based approach for life in society within an educational institution. The methodology used was qualitative, basic research type; given the adopted approach, a phenomenological design and inductive method were employed. The sample consisted of six teachers, and data collection techniques included interviews and documentary analysis. The results showed that the competency-based approach allows students to develop practical skills and competencies for the workforce, in addition to theoretical knowledge. The need to train teachers according to current challenges was emphasized. The study concludes that values and attitudes are essential for preparing students in times of change, which requires new knowledge, practical skills, and a strong moral character. In this regard, teachers must not only master what and how to teach but also have a deep understanding of their role as active agents in the construction and transformation of knowledge, adapting to a society in constant change and transformation.